IMPROVEMENT OF MANAGEMENT ACCOUNTING OF ENTREPRENEURIAL ACTIVITY IN INTERNATIONAL TOURISM - D. Rozhkova (Вестник университета)
The system of management accounting of entrepreneurial activity, which includes management of processes: entering new markets, innovative activity, prediction and risk assessment have shown. Within the framework of the implementation of management accounting systems it is proposed to reform the existing organizational structure of the tourism organization. The expediency of allocation of various centers of financial responsibility for a tour operator and travel agent have been proved. The article presents the matrix of key performance indicators and shows the author's version of the centers of financial responsibility for tourism organization.